Purification and characterization of the acyltransferase involved in biosynthesis of the major mycobacterial cell envelope glycolipid - monoacylated phosphatidylinositol dimannoside - Svetlíková, Zuzana (2014)
Phosphatidylinositol mannosides are essential structural components of the mycobacterial cell envelope. They are implicated in host-pathogen interactions during infection and serve as a basis for biosynthesis of other unique molecules with immunomodulatory properties- mycobacterial lipopolysaccharides lipoarabinomannan and lipomannan. Acyltransferase Rv2611 is involved in one of the initial steps in the assembly of these molecules in Mycobacterium tuberculosis - the attachment of an acyl group to position-6 of the 2-linked mannosyl residue of the phosphatidylinositol mannoside anchor. Although the function of this enzyme was annotated 10 years ago, it has never been completely biochemically characterized due to lack of the pure protein. We have successfully overexpressed and purified MSMEG_2934, the ortholog of Rv2611c from the non-pathogenic model organism M. smegmatis mc(2)155 using mycobacterial pJAM2 expression system, which allowed confirmation of its in vitro acyltransferase activity, and establishment of its substrate specificity.